An Insight into Isotherm Models in Physical Characterization of Adsorption Studies - Bbumba, Simon; Karume, Ibrahim; Nsamba, Hussein K.; Kigozi, Moses; Kato, Maxmillian (European Journal of Applied Sciences, 2024)
Here in, we review the adsorption isotherm models and the related statistical and error functions that give a mechanistic insight relating adsorption capacities with the adsorbate concentration and nature of the adsorbent surface. One, two and three-parameter isotherms are discussed in addition to isotherms that anticipate mono and multilayer adsorption surfaces. The isotherms such as Langmuir, Freundlich, Toth, Dubinin–Radushkevich, Sips, Temkin, Brunauer–Emmett–Teller, and Redlich–Peterson (R-P), and their combined forms have been addressed. Non-linear regression gives an accurate interpretation of the adsorption process with low error values compared to linear regression. The correlation coefficient as a tool to choose the best isotherm model is assessed with the Chi test which gives information about the fit with the best quality as well as the ANOVA that describes the significance of variance of the different error functions. Further, the different physiochemical parameters that affect the adsorption process are discussed.